Age dependency for coagulation parameters in paediatric populations - Toulon, Pierre; Berruyer, Micheline; Brionne-François, Marie; Grand, François; Lasne, Dominique; Telion, Caroline; Arcizet, Julien; Giacomello, Roberta; De Pooter, Neila (Thrombosis and Haemostasis, 2016)
Understanding of developmental haemostasis is critical to ensure optimal prevention, diagnosis, and treatment of haemorrhagic and thrombotic diseases in children. As coagulation test results are known to be dependent on the reagents/analysers used, it is recommended for each laboratory to define the age-dependent reference ranges by using its own technical condition. That study was carried out in seven centers to establish age-specific reference ranges using the same reagents and analyser. Plasma samples were obtained from 1437 paediatric patients from the following age groups: 15 days-4 weeks (n=36), 1–5 months (n=320), 6–12 months (n=176), 1–5 years (n=507), 6–10 years (n=132) and 11–17 years (n=262). Indication of coagulation testing was pre-operative screening for non-acute diseases in most cases. PT values were similar in the different age groups to those in adults, whereas longer aPTTs were demonstrated in the younger children. Plasma levels of all clotting factors, except for FV, were significantly decreased (p<0.0001) in the youngest children, adult values being usually reached before the end of the first year. The same applied to antithrombin, protein C/S, and plasminogen. In contrast, FVIII and VWF levels were elevated in the youngest children and returned to adult values within six months. The same applied to D-dimer levels, which were found elevated, particularly until six months of life, until puberty. These data suggest that most coagulation test results are highly dependent on age, mainly during the first year of life, and that age-specific reference ranges must be used to ensure proper evaluation of coagulation in children.
Keywords: Coagulation; childhood; paediatrics; reference ranges; developmental haemostasis